The Impact of a Six‐Year Climate Anomaly on the "Spanish Flu" Pandemic and WWI. (24th September 2020) - More, Alexander F.; Loveluck, Christopher P.; Clifford, Heather; Handley, Michael J.; Korotkikh, Elena V.; Kurbatov, Andrei V.; McCormick, Michael; Mayewski, Paul A.
Abstract: The H1N1 "Spanish influenza" pandemic of 1918–1919 caused the highest known number of deaths recorded for a single pandemic in human history. Several theories have been offered to explain the virulence and spread of the disease, but the environmental context remains underexamined. In this study, we present a new environmental record from a European, Alpine ice core, showing a significant climate anomaly that affected the continent from 1914 to 1919. Incessant torrential rain and declining temperatures increased casualties in the battlefields of World War I (WWI), setting the stage for the spread of the pandemic at the end of the conflict. Multiple independent records of temperature, precipitation, and mortality corroborate these findings. Plain Language Summary: A new, high‐resolution climate record from Europe shows a once‐in‐a‐century climate anomaly that occurred during the years of World War I and the Spanish flu pandemic. Mortality data from all causes show increases in times of worsening weather, precipitation, and temperatures, a factor in many of the major battles of WWI, as well as a possible exacerbating factor for the virulence of the pandemic. Key Points: Novel, high‐resolution climate record from Europe shows strong influx of marine air in a 1914–1918 climate anomaly unmatched in 100 years Independent precipitation, temperature, and historical records corroborate the timing and extent of the anomaly Historical and epidemiological records indicate that this climate anomaly affected the mortality in WWI as well as the "Spanish flu" pandemic